2019
DOI: 10.1097/md.0000000000014879
|View full text |Cite
|
Sign up to set email alerts
|

Immunocompetent patient with a brain abscess caused by Nocardia beijingensis in Latin America

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…Of these, 3 occurred in immunocompetent hosts, and all 3 were in Florida. [6][7][8][9][10] The most recent report by Chauhan, in 2019, was the only case in the United States that involved the CNS. 9 Ours is the second reported case of CNS nocardiosis in the United States, and the first with multiple simultaneous manifestations of disseminated nocardiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 3 occurred in immunocompetent hosts, and all 3 were in Florida. [6][7][8][9][10] The most recent report by Chauhan, in 2019, was the only case in the United States that involved the CNS. 9 Ours is the second reported case of CNS nocardiosis in the United States, and the first with multiple simultaneous manifestations of disseminated nocardiosis.…”
Section: Discussionmentioning
confidence: 99%
“…La lesión en la piel era un absceso, lo cual coincide con lo descrito en la literatura médica como resultado de la inoculación directa, que puede causar abscesos y celulitis localizada semejantes a los de la infección por Staphylococcus aureus o estreptococos. Se conoce un caso de nocardiosis con varios abscesos cerebrales en un paciente inmunocompetente internado en el Hospital Universitario Mayor -Méderi, en quien se aisló mediante técnicas moleculares Nocardia beijingensis y que finalmente falleció después de presentar compromiso multisistémico (10).…”
Section: Discussionunclassified
“…is known for its tropism to brain tissue and produces neurological symptoms such as: headache, nausea, aphasia, and hemiparesis [22]. Brain abscesses produced by nocardia on MRI studies are seen as areas of purulent necrosis, ring lesions consistent with abscess formation followed by necrosis and edema caused by vascular exudation and infiltration [20,22]. In the present study, MRI studies performed in the patient revealed similar lesions: rounded lesions at the level of the nuclei of the bilateral base, as well as, subcortical cortical lesions in the frontal lobes, parietal and temporal bilateral and at the level of the bilateral cerebellum and of different sizes on T2-weighted imaging (T2-WI) and FLAIR-WI.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Surgical treatment is necessary when collections exist [27]. Stereotaxic biopsy is crucial to make the diagnosis and obtain highly unpredictable antibiotic susceptibility [20,28], but craniotomy must be performed in patients with systemic infections and multiple brain injuries [5]. Aspiration and surgical excision may be indicated for abscesses>2.5 cm.…”
Section: Literature Reviewmentioning
confidence: 99%